2021
DOI: 10.1097/prs.0000000000007641
|View full text |Cite
|
Sign up to set email alerts
|

Robin Sequence: 5-Year Speech Outcomes—A Case-Control Study

Abstract: Background: Pierre Robin sequence (Robin sequence) is defined as the triad of micrognathia, glossoptosis, and airway obstruction. It is frequently associated with palatal clefting. In recent years, increased interest in speech outcomes of cleft patients diagnosed with Robin sequence has been shown. Methods: Speech outcomes of cleft patients with Robin sequence were assessed at age 5 in comparison with a cleft palate–only cohort. Speech parameters were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…. Other studies demonstrated cleft palate width to be an independent predictor for VPI in cleft lip and/or palate patients (Lam et In our previous cited studies the VPI rates found ranged from 0-58% in patients with RS Schwaiger et al, 2021). We observed higher rates of VPI in our RS-group (73%) and in our ICP-group (63%) compared to the literature.…”
Section: Discussionsupporting
confidence: 45%
“…. Other studies demonstrated cleft palate width to be an independent predictor for VPI in cleft lip and/or palate patients (Lam et In our previous cited studies the VPI rates found ranged from 0-58% in patients with RS Schwaiger et al, 2021). We observed higher rates of VPI in our RS-group (73%) and in our ICP-group (63%) compared to the literature.…”
Section: Discussionsupporting
confidence: 45%
“…That stated, there is data to suggest that palatal closure by 15 months of age prior to learning palate-related sounds is associated with improved speech and hearing (Rohrich et al, 1996;Shaffer et al, 2020;Kalmar et al, 2020). This data is also important in the backdrop of increasing reports of speech difficulties in the RS group (Stransky et al, 2013;Schwaiger et al, 2021). Age at palatoplasty in those studies was 9-13 months, and in neither study were cohorts treated with MDO.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Schwaiger et al 17 compared 51 patients with Robin sequence, including syndromic, to 128 patients with nonsyndromic CP only. Using the Cleft Audit Protocol for Speech-Augmented, which accounts for resonance, nasal airflow, and cleft speech characteristics, they reported higher rates of cleft speech characteristics in the Robin sequence group compared to their control.…”
Section: Discussionmentioning
confidence: 99%